Indeks Kualitas Air Sungai Noemuti dan Analisis Sensitivitas - Santiari, Made (BIO-EDU: Jurnal Pendidikan Biologi, 2019)
Noemuti River is a river located in the South Bikomi District with a length of 30 km that is monitored periodically by the North Central East Regency Environmental Service. Information on the results of this monitoring needs to be conveyed as simple information, one of which is in the form of a water quality index. This study aims to calculate the index value of water quality and conduct a sensitivity analysis. This research is a quantitative descriptive study using secondary data in the form of 2016-2018 monitoring results. The parameters included in the calculation of the water quality index are BOD, COD, TSS, Fecal Coliform, and Total Coliform. Data were analyzed using the pollution index formula to get a water quality index value. Sensitivity analysis was carried out with four scenarios, namely removing parameters a) Fecal Coliform b) Total Coliform c) Fecal Coliform and Total Coliform d) TSS. The Noemuti river water quality index value ranges from 0.26-5.28, with the category good quality to moderately polluted. Sensitivity analysis provides a picture of parameters that influences the water quality index value. The fourth scenario is a scenario that causes a change in the water quality index from the category of moderately polluted to lightly polluted on 2017 data in the second and third points. This means that TSS parameters must be considered to improve river water quality. Also, the loss of the Ci / Lij TSS value as the maximum value decreases the water quality index value means the maximum Ci / Lij value is very vital for the pollution index formula. From the results of the study, it can be concluded that the Noemuti river has been polluted, and TSS is a parameter that needs to be considered in arranging controlling water pollution recommendations.